Analysis Resilience, Competence, and Motivation to Increasing Performance Management: Mini Study Literature Review - Josua Panatap Soehaditama (Jurnal Multidisiplin Madani, 2023)
The purpose of this study was to examine the relationships between variables. This study used a literature review approach and collected several previous international papers. Data processing was not performed in this study, and it was a previous study that was helpful in that it was found that there was actually a significant relationship between variables, which is the novelty of this paper. A title like this study has never been studied before. This research brief on improving corporate performance requires a resilient, capable and motivated workforce that can rapidly improve management performance and achieve corporate goals. In general, any company that wants to be successful must have an agile foundation of talent. form an organization